2022
DOI: 10.3390/ijms23020732
|View full text |Cite
|
Sign up to set email alerts
|

Tilting the Balance: Therapeutic Prospects of CD83 as a Checkpoint Molecule Controlling Resolution of Inflammation

Abstract: Chronic inflammatory diseases and transplant rejection represent major challenges for modern health care. Thus, identification of immune checkpoints that contribute to resolution of inflammation is key to developing novel therapeutic agents for those conditions. In recent years, the CD83 (cluster of differentiation 83) protein has emerged as an interesting potential candidate for such a “pro-resolution” therapy. This molecule occurs in a membrane-bound and a soluble isoform (mCD83 and sCD83, respectively), bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 100 publications
1
12
0
Order By: Relevance
“…Amongst others, administration of sCD83 ameliorated disease progression in murine autoimmune models such as experimental autoimmune encephalomyelitis (EAE), systemic lupus erythematosus (SLE), inflammatory bowel disease (IBD) and antigen-induced arthritis (AIA) (6,15,24,25,50). Analogously, administration of sCD83 significantly improved graft survival in transplantation models of cornea, heart, kidney, and skin, which depended on the IDO1-mediated induction of Treg differentiation and proliferation (9,11,(51)(52)(53). In the present study, we report for the first time the pro-regenerative effects of sCD83 on cutaneous wound healing.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Amongst others, administration of sCD83 ameliorated disease progression in murine autoimmune models such as experimental autoimmune encephalomyelitis (EAE), systemic lupus erythematosus (SLE), inflammatory bowel disease (IBD) and antigen-induced arthritis (AIA) (6,15,24,25,50). Analogously, administration of sCD83 significantly improved graft survival in transplantation models of cornea, heart, kidney, and skin, which depended on the IDO1-mediated induction of Treg differentiation and proliferation (9,11,(51)(52)(53). In the present study, we report for the first time the pro-regenerative effects of sCD83 on cutaneous wound healing.…”
Section: Discussionsupporting
confidence: 55%
“…The membranebound form of CD83 (mCD83) expressed by TECs is absolutely essential for the positive selection and development of CD4 + T cells in the thymus (7). In addition, our group recently reported that mCD83 expression by Tregs is crucial for their development and that the specific deletion of CD83 on Tregs leads to exacerbated autoimmune pathologies and impaired resolution of inflammation (8,9). Furthermore, specific conditional KO CD83 in DC leads to excessive inflammatory immune responses and drastically increased autoimmunity (10).…”
Section: Introductionmentioning
confidence: 99%
“…Microarray analyses revealed that the Cd83 transcript is specifically induced in AAM but not CAM ( 7 ). The corresponding membrane bound CD83 (mCD83) glycoprotein, which is expressed on activated immune cells, has been described to have potent immunomodulatory properties ( 12 , 13 ). Furthermore, CD83 inhibits the ubiquitin-dependent degradation of MHC-II and CD86 on DCs as well as MHC-II on thymic epithelial cells, mediated by MARCH1 and MARCH8 respectively, thereby stabilizing the surface expression of these important molecules ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CD83 expressed by DCs and regulatory T cells (Tregs) plays a central role in promoting resolution of inflammation ( 16 , 17 ). In addition, a soluble isoform of CD83 (sCD83) has also been described, having profound immunomodulatory properties in murine autoimmune and transplantation models ( 12 , 13 , 18 , 19 ). Recently, we reported that sCD83 induces pro-resolving Mφ, thereby improving corneal transplant survival ( 20 ) as well as skin wound healing processes ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, research suggests that CD86 is a marker of DC activation, and CD83 is a specific marker of DC maturation. DC activation and maturation increase the expression of cell surface molecules CD86 and CD83, otherwise inhibit the differentiation and maturation of DCs, and reduce the expression of cell surface molecules CD86 and CD83 ( 16 19 ).…”
Section: Discussionmentioning
confidence: 99%